Psychological needs fulfillment and perinatal well-being among low-SES individuals: a mixed methods investigation - Alison F. Gammons; Charlotte V. Farewell; Chelsea Walker-Mao; Emma Ubriaco; Jenn A. Leiferman (Taylor & Francis Group, 2024)
Poor perinatal mental health is associated with deleterious effects and individuals with low socioeconomic status (SES) are at elevated risk. Fortifying multi-level resources of low-SES pregnant individuals to boost their well-being is a crucial step toward achieving equity in perinatal health. The purpose of this project was to explore what patterns of resources supported well-being among low-SES pregnant individuals in Colorado. In a prospective mixed methods cohort study, 23 low-SES pregnant individuals completed surveys and interviews. Participants were separated into 3 subgroups based on their overall Warwick-Edinburgh Mental Well-being Scale (WEMWBS) score and interviewed to identify multi-level resources that supported their well-being. Our analysis was framed by Self-Determination Theory which contends that three universal basic psychological needs are required for individuals to function in a healthy manner: autonomy, competence, and relatedness. We extrapolated resources that promoted perinatal competence, autonomy, and relatedness from the high well-being group. Perinatal-related knowledge (construct related to competence); mindfulness and intended pregnancy (constructs related to autonomy); and emotional, informational, and friend support, social capital, and connection to nature (constructs related to relatedness) were identified as the resources more frequently endorsed in the high well-being group. Targeting interventions to fortify specific multi-level resources that support the autonomy, competence, and relatedness of pregnant individuals facing socioeconomic disadvantage is a crucial step toward achieving equity in perinatal health.